The past of the outcaste :readings in dalit history - Bhattacharya, Sabyasachi,Ed; Yagati, Chinna Rao,Ed (Orient Blackswan, 2017)
Are you fit for political power even though you do not allow a large class of your own countrymen like the untouchables to use public school? … the use of public wells? … the use of public streets? … to eat any food they like? —B. R. Ambedkar, Annihilation of Caste These questions, raised by Dr Ambedkar roughly a century ago, still hold true. The prevalence of caste-based violence and rising Dalit assertion has led to a revival of the movement spearheaded by luminaries such as Phule, Ambedkar and others. To comprehend this rising revolution, it is important to trace writings of the public intellectuals and social scientists through history. The Past of the Outcaste brings together historical narratives of the ‘outcastes’, which together throw light on the economic, civil, cultural and political exclusion and discrimination that is caste-based. This collection includes statements on untouchability by leaders of the freedom movement—for example, Gokhale, Lajpat Rai, Ambedkar and Gandhi; essays on the history of the outcastes in the pre-colonial period; on the beginnings of Dalit consciousness and organized resistance to caste oppression; on the relationship between the nationalist movement and Dalits; and finally, essays locating the Dalits in the post-independence polity in India. This carefully edited compendium will be of use to students and scholars of history, sociology and political science in general and those in the area of ‘exclusion studies’ in particular.